Stress Effect of Food Matrices on Viability of Probiotic Cells during Model Digestion - Matouskova, Petra; Hoova, Julie; Rysavka, Petr; Marova, Ivana (Microorganisms, 2021)
The aim of this study was to evaluate the influence of model (alcohol, sugar, salt, protein and acid) and real foods and beverages on the viability of probiotics during incubation and artificial digestion. Viability of monocultures Lactobacillus acidophilus CCM4833 and Bifidobacterium breve CCM7825T, and a commercial mixture of 9 probiotic bacterial strains, was tested by cultivation assay and flow cytometry. In model foods, the best viability was determined in the presence of 0.2 g/L glucose, 10% albumin and 10% ethanol. As the most suitable real food for probiotic survival, complex protein and carbohydrate substrates were found, such as beef broth, potato salad with pork, chicken with rice, chocolate spread, porridge and yoghurt. The best liquid was milk and meat broth, followed by Coca-Cola, beer and coffee. Viability of probiotics was higher when consumed with meals than with beverages only. Addition of prebiotics increased the viability of probiotics, especially in presence of instant and fast foods. Generally, the highest viability of probiotics during artificial digestion was observed in mixed culture in the presence of protein, sugar and fat, or their combination. The increase of cell viability observed in such foods during model digestion may further contribute to the positive effect of probiotics on human health.
Keywords: food matrices; food stress; cell viability; probiotics; model digestion